Keteladanan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Al-Muslimun Pandan - Salim, Salim (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
School is an institution that is self-sufficient as a place to obtain knowledge. When you hear the word school mentioned, spontaneity comes to mind about devices that support the personal realization of smart, intelligent and wise people such as teachers, students, study buildings, friendly environments and so on. If the elements of school completeness have been met, then further attention will be paid to the quality and quality of the school. This matter will be assessed through the discipline, example, and scientific expertise of the teachers as well as school management by the Principal. One thing that is believed to be very important in improving the quality and quality of schools is to pay attention to teacher performance, and teacher performance is closely related to the role model played by the principal.